Numerical Simulation of Hydrodynamic and Sediment Transport in the Madura Strait - Muhammad Farhan Rahmat; Suntoyo; Widi Agoes Pratikto (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Surabaya serves as a coastal and economic center in East Java, where rapid coastal development around the Madura Strait has intensified sedimentation and shoreline change. Understanding hydrodynamic behavior and sediment transport is crucial for sustainable coastal management. This study applies a three-dimensional Delft3D numerical model to simulate hydrodynamics and sediment transport in the Madura Strait. The model accounts for tides, waves, wind, river discharge, temperature, salinity, and sediment properties to capture seasonal variations in circulation and sediment dynamics. Model validation using tidal and current observations shows acceptable accuracy based on RMSE and MAE values. Results indicate that tidal forcing predominantly controls current circulation, showing bidirectional flow with a phase lag between flood and ebb tides, leading to net sediment transport toward the Pamurbaya convergence zone. Significant wave heights (0.1–0.5 m) exhibit seasonal variation, increasing during the East Monsoon and the Second Transitional Season due to easterly winds. Sediment transport simulations show minor morphological changes (–0.02 to +0.02 m/year) but active redistribution, particularly near Pamurbaya. These findings highlight the dominant role of tidal dynamics and the need for adaptive, morphodynamic-based coastal management to ensure the long-term stability of the eastern Surabaya coastline.